2021
DOI: 10.21203/rs.3.rs-293044/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy in Decompensated Liver Cirrhosis: A Long-Term Follow-up Analysis of the Randomized Controlled Clinical Trial

Abstract: BackgroundMesenchymal stem cells (MSC) infusion was reported to improve liver function in patients with decompensated liver cirrhosis (DLC), however, whether the medication can improve outcome of these patients is poorly understand.MethodsThis prospective, open-labeled, randomized controlled study enrolled 219 patients with HBV-related DLC who were divided into control group (n=111) and umbilical cord-derived MSC (UC-MSC) treated group (n=108), then all of them received a follow-up check from October 2010 to O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…To the best of our knowledge, there is no specific drug for DLC and blocking the factors that cause further damage to liver cells is the basic treatment for post-hepatitis cirrhosis (12). Anti-HBV drugs, such as entecavir and tenofovir, can control the massive replication of HBV but cannot clear HBV, thus long-term antiviral treatment is required (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is no specific drug for DLC and blocking the factors that cause further damage to liver cells is the basic treatment for post-hepatitis cirrhosis (12). Anti-HBV drugs, such as entecavir and tenofovir, can control the massive replication of HBV but cannot clear HBV, thus long-term antiviral treatment is required (21).…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells are undifferentiated cells with the potential to differentiate into various cell types. The bone marrow contains hematopoietic stem cells, mesenchymal stem cells, endothelial progenitor cells and other undifferentiated cells (12). Once these undifferentiated cells from the bone marrow are transplanted into the liver with hepatocyte injury, they can differentiate into hepatocytes in the liver microenvironment, or they can secrete certain cytokines to promote the repair of damaged hepatocytes and improve liver function (13).…”
Section: Therapeutic Effect Of Autologous Bone Marrow Cells Injected ...mentioning
confidence: 99%
“…In a clinical trial, only after patients were infused with UCMSCs for 13 months did survival rates increase [111]. However, further research is needed to determine the precise mechanism by which UCMSC treatment improves survival only after 13 months of treatment.…”
Section: Pretreatment Of Mscsmentioning
confidence: 99%
“…Recently, mesenchymal stem cells (MSCs) as well as their derivates provide an alternative for patients with liver disorders. Various stem cells derived from human bone marrow (BMSCs), umbilical cord (UCSCs), and adipose tissue (ADSCs) has been utilized in the treatment of liver disease [10][11][12][13]. Both clinical and experimental evidences have shown that MSCs could e ciently protect hepatocytes by transdifferentiating into functional hepatocytes, secreting a wide range of immunosuppressive and trophic factors, and exosomes through autocrine or paracrine effects, leading to an anti brotic effect and promote liver regeneration [11,14].…”
Section: Introductionmentioning
confidence: 99%